2013
DOI: 10.1037/a0033988
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between work and nonwork self-aspects as a predictor of presenteeism and engagement: Cross-cultural differences.

Abstract: Research on the work-life interface does not specifically account for how individuals cognitively conceptualize their work and nonwork lives in terms of the differentiation between work and nonwork self-aspects. In addition, no cross-cultural research examines self-concept differentiation in conjunction with employee outcomes of presenteeism and engagement, pointing to a need to study these relationships cross-culturally. Results of the current study revealed cultural differences in self-concept differentiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 64 publications
0
33
0
2
Order By: Relevance
“…Empirical research provides evidence that country characteristics play a significant role in the loss of productivity due to presenteeism (Knies, Candel, Boonen, Evers, Ament, & Severens, 2012). Other studies have found cross-cultural differences for mental and physical presenteeism between Indian and US employees (Garczynski, Waldrop, Rupprecht, & Grawitch, 2013) and also between British and Chinese workers . In fact, the way people cognitively organize their daily lives varies from culture to culture.…”
Section: Work/ Family Conflictmentioning
confidence: 96%
“…Empirical research provides evidence that country characteristics play a significant role in the loss of productivity due to presenteeism (Knies, Candel, Boonen, Evers, Ament, & Severens, 2012). Other studies have found cross-cultural differences for mental and physical presenteeism between Indian and US employees (Garczynski, Waldrop, Rupprecht, & Grawitch, 2013) and also between British and Chinese workers . In fact, the way people cognitively organize their daily lives varies from culture to culture.…”
Section: Work/ Family Conflictmentioning
confidence: 96%
“…The concept of engagement The concept of engagement has been studied from various disciplines, including sociology (Morimoto and Friedland, 2013), psychology (Garczynski et al, 2013), educational psychology (Saveanu and Saveanu, 2012), organisational behaviour (Kataria et al, 2013;Margolis and Molinsky, 2008), and marketing Hollebeek, 2011). Irrespective of the discipline, the concept of engagement implies three features (Hollebeek, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…depression) presenteeism. The authors conclude that mental presenteeism is more likely to have a significant negative association with work engagement because taking a sick day due to a physical ailment is more likely to be accepted in the workplace (Garczynski, Waldrop, and Rupprecht & Grawitch, 2013). Though research concerning the relationship between employee engagement and presenteeism is limited, there currently appears to be agreement that employee engagement is negatively related to presenteeism.…”
Section: Employee Engagement and Presenteeismmentioning
confidence: 97%